The inhabited woman : a novel - Belli, Gioconda, 1948- (Americas (Madison, Wis.), 2004)
In the mesmerizing storytelling tradition of Isabel Allende, Gabriel Garcia Marquez, and Laura Esquivel comes Gioconda Belli. Like her shining predecessors, Belli brilliantly captures the heart of her people and the passion of her country with a distinctive brand of magical realism: lyrical yet earthbound ... romantic yet suspenseful ... consistently original. Lavinia is THE INHABITED WOMAN: accomplished, independent, fiercely modern. A successful architect living in the capital of her Latin American country, Lavinia is sheltered and self-involved--until the spirit of an Indian woman warrior enters her being. Now Lavinia's blood pulses with the tumult of ancient uprisings; now her soul is lit by the vision of long-dead rebels. Abandoning privilege, she dares to join a revolutionary movement against a violent dictator and--through the power of love--finds the courage to act.